Cytotoxic constituent of Melicope latifolia (DC.) T. G. Hartley - Lim, Pei Cee; Ali, Zulfiqar; Khan, Ikhlas A.; Khan, Shabana I.; Kassim, Nur Kartinee; Awang, Khalijah; Shaari, Khozirah; Ismail, Amin (Taylor and Francis, 2022)
An undescribed conjugated sesquiterpene, amelicarin (1), together with nine known compounds (2–10) were isolated for the first time from Melicope latifolia. Their structures were elucidated by extensive NMR spectroscopic and mass spectrometric methods. The conjugated sesquiterpene possesses a unique 6/6/9/4-ring fused tetracyclic skeleton. The proposed biosynthesis pathway of 1 consist of three reactions steps: (1) polyketide formation, (2) cyclisation and (3) addition to form the conjugated sesquiterpenoid as final metabolite. Out of the ten isolated metabolites, amelicarin (1) showed activity against 4 cancerous cell lines namely SK-MEL skin cancer, KB oral cancer, BT-549 breast cancer, and SK-OV-3 ovarian cancer with IC50 values between 15 and 25 µg/mL.